Livestock impact pathways—Needs, targeting, up front investments are important - International Livestock Research Institute (International Livestock Research Institute, 2011)
On 9 and 10 November 2011, the ILRI Board of Trustees held a 2-day 'liveSTOCK Exchange' to discuss and reflect on livestock research for development. In a session on livestock impact pathways, participants discussed ways to enhance ILRI efforts on capacity development, knowledge, gender, communication, partnerships and innovation platforms. Some feedback from the group discussions included: that a lot of what we do leads to information, that we often employ 'wide shotgun' approaches and that we need to adopt more 'end user' perspectives on our information, to be more needs-based. Regarding communication and capacity building, we need to pay much more up-front attention in projects; and finally that an innovation platform is maybe a 'sound way' to combine all the elements.